The effect of interest rates on the demand for mortgage credit in South Africa - Earl, Gemma (School of Economics, 2025)
This paper uses novel and detailed mortgage origination data to estimate the interest rate elasticity of mortgage demand along the intensive margin in South Africa. I find that homebuyers increase the size of the mortgage they take out by 2.8 percent in response to a 1 percentage point decrease in the prime interest rate. Additionally, I explore the effect on housing demand since homebuyers may adjust their housing preferences when interest rates change. I find that homebuyers purchase 2.3 percent more expensive properties. The resultant impact on the degree of mortgage leverage is economically small. These findings have implications for monetary policy transmission in the housing market and financial stability more generally.